The value of a small urban green area to the medium and large-sized mammals conservation (Research, Society and Development, 2021)
Brazil presents the biggest mammal diversity in the world, 755 species, of which 110 are classified under some degree of threat. In the São Paulo State is an estimated 350 taxa richness, however, this number can be even higher due to the gap of sampling over large extensions. In addition, many urban green areas are not studied because their value is underestimated for biodiversity conservation. In this way, the present study aimed to survey the medium and large-sized terrestrial mammals in a Municipal Conservation Unit located in the urban area of Franca, SP. Using cameras trap, sand plots, and active search, in the period between May and July 2019, 16 mammals were sampled. The highest number of species was identified through sand plots (12), followed by active search (7) and cameras trap (4). The sampled community is mostly composed of opportunistic and generalist species with few predators. Among species found, the maned wolf (Chrysocyon brachyurus) is classified nationally as vulnerable to extinction. Despite the significant number of sampled species, the species accumulation curve obtained did not reach its asymptote. Thus, it is concluded that Zoobotanic Garden, despite suffering strong anthropic pressure, develop an important role in the regional medium and large-sized terrestrial mammals conservation, acting as a refuge area for these species.